GAYA KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN SEKOLAH TINGGI PERIKANAN JAKARTA - Alvia Imritum Sanika; Tatag Herbayu (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
This study aims to determine whether there is influence between leadership and communication styles on employee performance at the Jakarta Fisheries College. This type of research is Explanatory Research with a quantitative approach. The population in this study were all permanent employees, namely ASN at the Jakarta. The result analysis there is influence between style leadership and communication on employee performance partially. Leadership style and communication simultaneously and significantly influence employee.